Suture holding capacity of the Achilles tendon during the healing period: An in vivo experimental study in rabbits - (:unkn) unknown (SAGE PUBLICATIONS INC, 2006)
Background: Early motion and weightbearing is known to promote the healing of Achilles tendon repair. It is important to be informed about the repair strength for a secure rehabilitation. There are reports about the initial repair strength of Achilles tendons; however, they are mainly in vitro studies that represent the time zero strength of the repair. Softening of the tendon observed during the biological process of the tendon healing, which may effect the suture holding capacity and in turn the repair strength of the tendon has not been evaluated before. Methods: In the current study, the suture holding capacity of rabbit Achilles tendon was observed at various times during the healing period. Results: The suture holding capacity of the tendon at the end of the first and third weeks after surgery was found to be similar within 30% of the control tendon. However, at the end of the fourth week it was doubled reaching 65% of the control tendon. Conclusions: Intrinsic tendon insufficiency which causes a decrease in the suture holding capacity of the tendon may lead to pull-out of the suture material during the postoperative third week. This period is precarious for early motion and weightbearing since the suture holding capacity of the tendon doubled relative to the previous three weeks.
Keywords: achilles; experimental; suture holding capacity; TENSILE-STRENGTH; REPAIR; RUPTURE; SEPARATION; VITRO; ENDS